Gold nanoparticle-based novel visual diagnostic method for the detection of specific IgE to test for food allergies. Issue 19 (28th April 2016) - Bose, Partha Pratim; Mandal, Gautam; Chatterjee, Urmimala; Singh, Meenu; Chatterjee, Bishnu Pada
Abstract : Visual test for food allergy by GNP-based plasmonic detection of specific IgE in sera. Abstract : Food allergies are recognized as a major public health issue, especially in early childhood, with no preventive treatment. The diagnosis of food allergies currently relies on careful study of the patient's history and diagnostic tests such as the skin prick test (SPT), serum specific IgE (immunoglobulin E) testing and, if indicated, oral food challenges, which are often risky. In this study, a sandwich-type immunocomplex was formed between different food allergens, specific IgE from sera and secondary anti-IgE conjugated with the enzyme horseradish peroxidase. Gold(iii ) chloride was subsequently added as a visual reader reagent. The color change from red to blue and the associated change in intensity at 550 nm was proportional to the concentration of remaining hydrogen peroxide after decomposition by horseradish peroxidase, which in turn triggers the aggregation of gold nanoparticles generating a blue color with a decrease in intensity at 550 nm. The generation of the visible blue color reports the presence of allergy issues compared to the red color in healthy subjects, and the consequent drop in intensity at 550 nm measures the amount of serum specific IgE, which corroborated the SPT results from the corresponding patients. This multiplexed visual diagnostic system for specific IgE against different food allergens using plasmonic phenomena of the aggregated gold nanoparticles has been a rapid, cheap, sensitive and high through put assay for the detection and determination of the severity of food allergens with a very low sample requirement (5 μl).